2023
DOI: 10.1002/lpor.202200955
|View full text |Cite
|
Sign up to set email alerts
|

Diatomic Metasurface for Efficient Six‐Channel Modulation of Jones Matrix

Abstract: Multi‐channel modulation of Jones matrix facilitates encoding a variety of different functions in metasurfaces. However, multiple channels are usually accompanied by a high system complexity and a low efficiency. Here, a compact and effective diatomic metasurface platform that can impose the six‐channel modulation of Jones matrix efficiently is proposed. The metasurface consists of two anisotropic nanopillars with exquisitely designed structural sizes and rotation angles with near‐unity transmission. To verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, it is difficult to develop a universal approach to design such a metasurface due to the high transmission rate of dielectric material, the conventional modulating methods for dielectric materials based on Mie resonance, etc., limiting the structural degrees of freedom and making it difficult to additionally modulate the polarization on this basis. A supercell consisting of multiple anisotropic nanopillars is used to overcome the modulation limit of the Jones matrix of the meta-atom metasurface [43][44][45]. If no coupling exists between the nanopillars, the total transmission rate of each nanopillar can be expressed as E out = ∑ i=1 E outi , where i is the index of the i-th nanopillar.…”
Section: Design Of Polarization Selective Metasurfacementioning
confidence: 99%
“…However, it is difficult to develop a universal approach to design such a metasurface due to the high transmission rate of dielectric material, the conventional modulating methods for dielectric materials based on Mie resonance, etc., limiting the structural degrees of freedom and making it difficult to additionally modulate the polarization on this basis. A supercell consisting of multiple anisotropic nanopillars is used to overcome the modulation limit of the Jones matrix of the meta-atom metasurface [43][44][45]. If no coupling exists between the nanopillars, the total transmission rate of each nanopillar can be expressed as E out = ∑ i=1 E outi , where i is the index of the i-th nanopillar.…”
Section: Design Of Polarization Selective Metasurfacementioning
confidence: 99%
“…Polarization, as one of the important properties, is the fundamental dimension used to characterize electromagnetic waves in free space [1]. A Jones matrix with a standard 2 × 2 configuration can be employed to describe the polarization state, where each component represents a unique mapping from the input polarization to the output polarization [2][3][4]. * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is active depth-detection that employs a light source to illuminate a target object and requires many optical components, which hinders the miniaturization process. The second method is passive depth detection, which acquires depth information in the presence of ambient light, thereby reducing the size to some extent. Therefore, further compressing the optical components is vital to minimize the footprint of the passive depth-detection systems. Metasurfaces, as two-dimentional metamaterials, offer a potent and lightweight platform for light manipulation. Moreover, metalenses, which are primarily employed in imaging, exhibit remarkable functionalities. Numerous single-lens cameras based on metalenses have been developed for compact integration. Specifically, some studies have demonstrated that metalenses based on two interleaved off-axis focal spots or a DH-PSF exhibit superior accuracy in depth recovery for single-lens passive depth detection. As diffractive optical elements, the metalenses used for depth detection suffer from significant chromatic aberrations. Therefore, the incorporation of filters is essential for obtaining narrowband light.…”
Section: Introductionmentioning
confidence: 99%